Desperately seeking revenue - Rosanne Altshuler; Katherine Lim; Roberton Williams (Rutgers University, Department of Economics, 2011)
In August 2009 the Congressional Budget Offi ce warned that the budget was on an unsustainable path. Preventing federal debt from growing faster than the economy over the long-run requires large increases in revenues and/or decreases in spending. We explore, using the Urban-Brookings Tax Policy Center Model, whether incremental reforms of the current tax system could raise enough revenue to reduce the deficit to a sustainable level over the last fi ve years of the current 10-year budget window. We conclude that feasible tax increases within the current tax structure cannot generate suffi cient revenues to bring federal budget defi cits under control.
Keywords: H20; H60; 330; budget deficit; tax reform; individual taxation; Steuerreform; Steueraufkommen; Haushaltskonsolidierung; USA